Overall Survival of Elderly Patients Having Surgery for Colorectal Cancer Is Comparable to Younger Patients: Results from a South Asian Population. (11th July 2017) - Chandrasinghe, Pramodh Chitral; Ediriweera, Dileepa Senajith; Nazar, Thaaqib; Kumarage, Sumudu; Hewavisenthi, Janaki; Deen, Kemal Ismail
Abstract : Introduction . There has been a continuous debate on whether elderly patients with colorectal cancer (CRC) fair worse. The aim of this study is to assess the thirty-day mortality (TDM) and overall survival (OS) of elderly patients undergoing surgery for CRC. Method . OS between two groups (≥70 versus <70 years) having surgery for CRC was analyzed. Demographics, tumour characteristics, and serological markers were considered as independent factors. Multivariable analysis was done using the Cox proportional hazard model. We also compared overall survival in the elderly versus those <60 and <50 years. Results . 477 patients, 160 elderly (55% male; median age 75, range 70–89) and 317 younger patients (49% male; median age 55, range 16 to 69), were studied. Overall survival in CRC patients ≥70 is comparable to <70 (P = 0.45 ) and <60 years (P = 0.08 ). Poor OS was observed in the ≥70 versus <50 years (P = 0.03 ). TDM in the elderly was poor (P < 0.05 ). Postoperative cardiac complication was the only determinant affecting survival in the elderly (P = 0.01 ). Conclusion . OS in elderly CRC patients having surgery is not worse compared to <70 and <60 years although the TDM was higher. Postoperative cardiac complications significantly affected OS in those ≥70 compared to those <50 years. Chronological age alone should not negatively influence surgical decision-making in the elderly.